2006
DOI: 10.1016/j.pbb.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal intravenous nicotine administration on locomotor behavior in pre-weanling rats

Abstract: Maternal tobacco use is associated with adverse developmental outcomes in offspring, including hyperactivity. Animal studies attempting to model this phenomenon have primarily used continuous s.c. nicotine infusion as the method of nicotine administration, which does not model the intermittent bolus delivery of nicotine associated with smoking in humans. The purpose of the present experiment was to examine the locomotor activity of pre-weanling offspring of pregnant rats exposed to an i.v. nicotine dosing prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
71
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 48 publications
11
71
1
Order By: Relevance
“…Our results indicate that prenatal nicotine exposure results in elevated anxiety and depression in the young rat offspring. These results are in agreement with that of a recent study [63] that reported open-field hypoactivity in gestational nicotine-exposed rats. Other reports have also shown the presence of anxiety with elevated plus-maze test in older adolescent rats being about 40 days old [17,21].…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicate that prenatal nicotine exposure results in elevated anxiety and depression in the young rat offspring. These results are in agreement with that of a recent study [63] that reported open-field hypoactivity in gestational nicotine-exposed rats. Other reports have also shown the presence of anxiety with elevated plus-maze test in older adolescent rats being about 40 days old [17,21].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other reports LeSage et al, 2006), the results of the locomotor activity experiment revealed that nicotine initially induced hypoactivity, followed by hyperactivity across repeated injections. More important, although there was little evidence indicative of cross-sensitization to the initial methylphenidate challenge following nicotine exposure, nicotine pre-exposure promoted the induction of locomotor sensitization following three repeated methylphenidate injections.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings for prenatal smoking and birth weight concur with results from experimental animal studies (10,11,24) and studies of naturally conceived children (15). The existing literature for prenatal smoking and offspring antisocial behavior is less clear than that for birth weight, highlighting the need for novel designs in this area.…”
Section: Discussionsupporting
confidence: 81%
“…Consider the example of smoking in pregnancy, which is associated with a number of adverse outcomes in offspring including reduced birth weight and increased antisocial behavior. Plausible physiological mechanisms have been suggested to explain these associations (8)(9)(10)(11). However, smoking in pregnancy is influenced by maternal characteristics as well as by maternal genotype (6,8,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation